Penguatan Kelembagaan Dalam Pencegahan dan Pengendalian Kebakaran Hutan dan Lahan di Kabupaten Muaro Jambi Provinsi Jambi - Suhendri, Suhendri; Purnomo, Eko Priyo (Journal of Governance and Public Policy, 2017)
Forest fires and land accompanied by smoke disaster that struck Jambi province Muaro khussnya inJambi that impact on the health, environmental and economic well in Indonesia maupaun in neighboringcountries, Malaysia and Singapore. The aim of this study was to analyze shopped mendriskripsikan andinstitutional strengthening in the prevention and control of land and forest fires in Jambi Province JambiMuaro. This research uses descriptive study with a qualitative approach. The focus of research isinstitutional strengthening in the prevention and control of forest fires and land. The result of thisresearch is the institutional strengthening in the prevention and penegendalian land and forest fireshave not been effective. The advice given was on fire control should at this stage of prevention andenforcement of preventive measures against fire for deterrent effect.